ANALISIS PERTUMBUHAN LINIER KORAL DAN KORELASINYA DENGAN VARIASI SUHU PERMUKAAN LAUT TAHUNAN STUDI KASUS KORAL DARI PERAIRAN PULAU SIMEULUE - Eltrik, Mustika
Coral is able to record the environmental parameters e.g . sea surface temperature (SST). SST variation of West Sumatra Sea is influenced by the monsoon system,the maximum SST is ± 31?C during the northeast monsoon and the minimum SST ± 27?C during the southwest monsoon. SST variation is expected to affect linear growth of coral. This study aimed to analyze annual linear growth (extention) of coral and its correlation to the annual variations of sea surface temperature (SST). Coral samples are obtained from Research Centre for Geotechnology, Indonesian Institute of Sciences (LIPI). Those samples were taken from three locations in Simeulue Islands waters in 2007: i.e SM 1, SM 2 and SM 3 and water depth of 3, 10, and 10 m respectively. SPL data used in this study is from the satellite AVHRR (Advanced Very High Resolution Radiometer) with resolution of 4x4 km and period of years 1989 to 2007. Monsoon strength is expressed in a Webster Yang Index (WYI) in June -July –August (JJA) and period of year 1989-2007. To calculate annual linear extention of coral is used CoralXDS software.Data input is a digital image x-ray scanned of coral samples. Linear regression is used to model the correlations between two variables i.e. SST and linear extention by using linear equations of theregression Based on the analysis of the density banding of three samples are obtained corals age i.e SM 1 is 10 years (1998-2007), SM 2 is 19 years (1989-2007), and SM 3 is 15 years (1993-2007). The average annual linier extention rate of the three samples is as follow: SM 1 (1.2 cm/year), SM 2 (0.75 cm/year), and SM 3 (1.3 cm/year). Coefficient correlation of coral annual linear extention and SST show moderate correlation i.e SM 1 r = -0.56, r = -0.33 SM 2 and SM 3 r = -0.401. The optimum temperature for the linear extention of corals in this study area isranges from 29,1 to 30,5?C. SST annual variation in Simeulue is quite influenced by monsoon variations , especially in SM 2 which is shown a medium level of correlation between WYI and SPL (r = -0.31). SST at SM3 site strongly correlates with Indian Ocean Dipole (r = -0.3).